Diversity of culturable endophytic fingi isolated from Mangrove leaves in Iloilo River. - Lirazan, Lauren Anais M.
Endophytic fungid are known to be a diverse group of organisms, many of which have not been identified and classified. Due to their diversity and potential in producing secondary metabolites, many studies have been conducted to identify, classify and characterize these fungi. This project generally aimed to study the fungal endophyte assemblages of leaves from mangroves (Avicennia rumphiana, A. officinalis, Heritiera littoralis, Xylocarpus granatum) in Iloilo River, Iloilo City. Specifically, it aimed to: Isolate, identify, and classify the endophytic fungi from selected mangrove species; b) determine the species richness of endophytic fungi; and c) Identify the dominant endophytic fungal taxa. Leaf segments were plated on saltwater PDA plates amended with penicillin streptomycin. Seven distinct taxa were isolated and five were identified to the species level. Majority of the isolated taxa were ascomycetes with Absidia glauca being the dominant endophytic fungus unlike in other studies. However, Aspergillus species were numerous consistent with other reports. This is the first study on the fungal endophytes from mangroves in Iloilo River, Philippines.